Processo da ambidestria em transições tecnológicas - Souza, Aruana Rosa (Universidade do Vale do Rio dos Sinos, 2017)
Discontinuous changes in the market cause companies to search for new technologies. Ambidexterity supports companies during periods of technological transitions, enabling them to achieve the maximum of excellence in the management of new technologies, essential for new markets entrance, and traditional technologies, useful for maintaining the company in markets they already are. Although this literature has been extensively studied for more than 20 years, few studies have deepened on how firms are ambidextrous during the technology transition process This study analyzed a knowledge-intensive ambidextrous company that underwent two technology transition cycles in less than 6 years. A single case study was conducted in a Brazilian company in the information technology sector. As a result of the investigation, it was found that the decision of the company to become ambidextrous was motivated by critical factors that arose mainly by the company's need to enter new businesses. Also, there was a reduction in transition cycles as the company gained experience in the process of incorporating new technologies and maturity of ambidextrous business management. Context factors were important, once they supported managers and employees in short, medium and long-term actions during transitions. This work contributes to the theoretical perspective by revealing in practice how an IT company simultaneously manages new business and traditional business during critical times of technological transitions. It also looked at how a company has organized itself in terms of processes, cultures, structures and routines to adapt to the changing environment. With regard to managerial contributions, this study guides managers to reflect on their business, elucidating different types of ambidextrous structures that an organization can choose, and helps companies to structure and devise an action plan focused on strengthening weaknesses. Furthermore, this study elucidates managers and employees profiles considered competitive in organizations that choose to structurally separate new and traditional business management.
Keywords: Ambidestria; Exploração; Explotação; Transição tecnológica; Tecnologia da informação; Ambidexterity; Exploration; Exploitation; Technological transition; Information technology; ACCNPQ::Ciências Sociais Aplicadas::Administração